Optimizing the Performance of the Tegal Police Kamsel Unit Through Dikmas Lantas to Increase Awareness of Drivers with Disabilities in Ownership of a SIM (Advances in Police Science Research Journal, 2024)
Along with the increasing population followed by rapidly developing technology at this time, transportation, especially motorized vehicles, is a necessity for the people of Indonesia today. Drive motorized vehicles by the community in general to meet daily needs such as work and education. Even though people can easily drive motorized vehicles, there are rules that must be obeyed by every driver. One of them is the ownership of a SIM, including drivers who are persons with disabilities. Tegal Regency itself has 12,871 people who are persons with disabilities. Persons with disabilities in Tegal Regency also have the same opportunity to have a driver's license to drive a motorized vehicle to fulfill their daily needs. Based on the applicable and most recent regulations, namely the Telegram Letter Number: ST/1938/Yan.1.1./2022 dated 9 September 2022 regarding instructions for issuing SIMs for persons with disabilities, there are around 6,353 people who are persons with disabilities in Tegal Regency who can have a SIM but it turns out that SIM applicants at the Tegal Police Satpat are still lacking. To describe these problems, the authors conducted qualitative research with field studies. So that the discussion is right on target and not widened, the authors provide a research focus on the object under study, namely the performance of the Kamsel unit through Dikmas then to increase the awareness of drivers with disabilities in owning a SIM. In describing these problems, the author uses management theory from George R. Terry, specifically on the POAC theory and 6M theory and is assisted by the concept of Dikmas Discourse and the rules that apply related to the implementation of Dikmas Disadvantage for persons with disabilities. In general, the implementation of direct dikmas by the Tegal Polres Kamsel Unit has not complied with the applicable procedures. It can be seen in the planning, organizing, implementing, and monitoring that are not fully in accordance with the expected conditions. Then, looking at the resources owned by the Tegal Polres Kamsel Unit, there are still many deficiencies. Therefore the author also formulates various solutions to problems related to these problems. By solving this problem, it is hoped that the research objectives can be achieved, namely increasing the awareness of drivers with disabilities in owning a driver's license.
Keywords: SIM; Unit Kamsel; Dikmas; Disability